2020
DOI: 10.1080/23723556.2020.1805256
|View full text |Cite
|
Sign up to set email alerts
|

CX-5461 can destabilize replication forks in PARP inhibitor-resistant models of ovarian cancer

Abstract: Acquired drug resistance leads to poor clinical outcome in high grade serous ovarian cancer (HGSOC). We have demonstrated the efficacy of the novel drug CX-5461 in HGSOC is mediated through destabilization of DNA replication forks. The data highlights the potential of CX-5461 in overcoming a general mechanism of chemotherapeutic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A phase I REPAIR trial, combining CX-5461 and the PARP inhibitor talazoparib, is underway to treat patients with metastatic castration-resistant prostate cancer (mCRPC) (ClinicalTrials.gov Identifier: NCT05425862). Initially recognized for its specific blockade of Pol I transcription by disrupting SL1-rDNA association ( 271 ), subsequent studies have unveiled that CX-5461 binds to and stabilizes G-quadruplex DNA structures, impeding replication forks and inducing DNA breaks ( 270 , 276 , 277 ). Although studies propose that the primary mechanism of CX-5461 involves topoisomerase II poisoning ( 276 ), a recent study suggested that CX-5461 primarily targets the initiation of Pol I by irreversibly inhibiting the release of RRN3 from the pre-initiation complex on the rDNA promoter.…”
Section: Targeting Ribosome Biogenesis For Cancer Therapeuticsmentioning
confidence: 99%
“…A phase I REPAIR trial, combining CX-5461 and the PARP inhibitor talazoparib, is underway to treat patients with metastatic castration-resistant prostate cancer (mCRPC) (ClinicalTrials.gov Identifier: NCT05425862). Initially recognized for its specific blockade of Pol I transcription by disrupting SL1-rDNA association ( 271 ), subsequent studies have unveiled that CX-5461 binds to and stabilizes G-quadruplex DNA structures, impeding replication forks and inducing DNA breaks ( 270 , 276 , 277 ). Although studies propose that the primary mechanism of CX-5461 involves topoisomerase II poisoning ( 276 ), a recent study suggested that CX-5461 primarily targets the initiation of Pol I by irreversibly inhibiting the release of RRN3 from the pre-initiation complex on the rDNA promoter.…”
Section: Targeting Ribosome Biogenesis For Cancer Therapeuticsmentioning
confidence: 99%
“…Acetylation of histone 4 at lysine 8 (H4K8) by the histone acetyltransferase PCAF (p300/CBP-associated) recruits the MRE11 nuclease to stalled forks, but PCAF activity has been reported as low in some BRCA2-deficient cells [142]. The RNA polymerase 1 inhibitor CX-5461 has also been demonstrated to overcome replication fork protection in patient-derived xenograft (PDX) models of HRR-deficient HGSOC involving MRE11 degradation of replication forks [143,144]. Down-regulation of the de-ubiquitylating enzyme USP1 (ubiquitin specific peptidase 1) in BRCA1-deficient cells leads to replication fork destabilisation in a synthetic lethal manner and may be another strategy to address PARPi resistance in HRR deficient tumour cells that have undergone stabilisation of the DNA replication fork [145,146].…”
Section: Stabilisation/destabilisation Of the Dna Replication Forkmentioning
confidence: 99%